TiO2-enhanced chitosan/cassava starch biofilms for sustainable food packaging - Gomes de Menezes, Francisco Leonardo; Henriquede Lima Leite, Ricardo; Gomes dos Santos, Francisco Klebson; Aria, Adrianus Indrat; Mendes Aroucha, Edna Maria (Elsevier, 2021)
Biopolymeric films with the addition of nanoparticles have been studied as an alternative to replace petroleum-based synthetic packaging, which is difficult to recycle and leads to a major environmental problem. The goal of this study is to develop and characterise biopolymeric films of chitosan and cassava starch with the addition of titanium dioxide (TiO2) nanoparticles for use as food packaging. Chitosan film (2% w/w), cassava starch film (2% w/w), and chitosan/cassava starch (1:1) blend were developed in the absence and presence of TiO2 nanoparticles (0.25% and 1% w/w) and characterised in terms of physicochemical properties. The results indicate that the properties of films related to water (permeability, solubility, and water sorption) and mechanical (tension, elongation, and Young's modulus) are strongly influenced by the characteristics of the biopolymers used and can be improved with the introduction of TiO2. The water sorption was reduced with the addition of TiO2, which makes the film more hydrophobic and exhibits a higher tensile strength by more than 15% and elongation by more than 100%. The addition of 1% TiO2 also leads to a reduction in transmittance of 97% in UVA, UVB, and UVC regions, which is a valuable feature for food preservation.
Keywords: Bionanocomposite; Biopolymers; Titanium dioxide; Cassava starch; Chitosan